Integrasi Pembinaan Ibadah dan Literasi Keuangan bagi Mualaf dalam Program Pengabdian Masyarakat Internasional di Kampung Temaga Dayak - Siti Khadijah; Kholifuddin Roma; Nurma Sari (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2026)
The Muslim community in rural areas of Sarawak still faces limitations in worship guidance and financial literacy based on Islamic values. This study aims to describe the implementation of an international community service program that integrates worship guidance and financial literacy in Kampung Temaga Dayak. The method used is a descriptive qualitative approach through participatory observation, in-depth interviews, and documentation. The results of the study show that contextual worship guidance improves the community's understanding and practice of basic worship, while financial literacy education through the introduction of the concepts of murabahah and riba encourages enthusiasm and reflective dialogue regarding daily economic practices. The integration of these two aspects is effective in strengthening the internalization of Islamic values and supporting the independence of the Muslim community.